Inorganic / organic hybrid material synergistically stable zinc-iodine battery and application thereof

By mixing zirconium hydrogen phosphate (ZPO) and phthalocyanine (PC) to form an inorganic organic hybrid interface layer, it is solved as the positive electrode material of zinc-iodine batteries, and the instability of iodine intermediates and the shuttle effect of water-soluble intermediates in zinc-iodine batteries is solved. The problem has significantly improved the cycle stability and service life of the battery.

CN119481360AActive Publication Date: 2025-02-18WEIFANG UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510058700.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-02-18
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

During the charging and discharging process of aqueous zinc-iodine batteries, due to the instability of the iodine intermediate and the shuttle effect of the water-soluble intermediate, the Coulomb efficiency is low, the capacity attenuation and the short cycle life.

Method used

The inorganic layered material zirconium hydrogen phosphate (ZPO) and the cyclic two-dimensional organic material phthalocyanine (PC) are fully mixed to form an inorganic organic hybrid interface layer. As the positive electrode material, the high strength of ZPO and the flexible phase of PC are used. Combination to improve the phase interface fusion of composite materials.

Benefits of technology

It significantly improves the cycle stability and service life of zinc-iodine batteries, reduces the hydrolysis reaction of iodine intermediates and the shuttle effect of water-soluble intermediates, and improves the coulomb efficiency and capacity maintenance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481360A_ABST
    Figure CN119481360A_ABST
Patent Text Reader

Abstract

The invention discloses an inorganic / organic hybrid material synergistically stable zinc-iodine battery and application thereof, and belongs to the technical field of chemical energy batteries. The zinc-iodine battery comprises a positive plate, a negative plate and an electrolyte, the positive plate contains an inorganic / organic hybrid material composed of a layered inorganic material and an annular two-dimensional organic material. The preparation method comprises the following steps: fully mixing a layered inorganic material and an annular two-dimensional organic material to obtain an inorganic / organic hybrid material; an inorganic / organic hybrid material, conductive carbon and a binder are ground and mixed, a current collector is coated with the mixture, then an I-active substance solution is dropwise added, and the positive plate is obtained. The layered inorganic material is zirconium hydrogen phosphate; the annular two-dimensional organic material is phthalocyanine. The inorganic-organic hybrid interface layer is prepared, and the high strength and high modulus of ZPO are combined with the flexibility of PC, so that the phase interface fusion of ZPO / PC is remarkably improved, shuttling of water-soluble intermediates is inhibited, the cycle stability of the battery is improved, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical energy batteries, and in particular to an inorganic / organic hybrid material synergistically stabilized zinc-iodine battery and applications thereof. Background Art

[0002] In order to meet the growing demand for portable electronic products and electric vehicles, the development of new electrochemical energy storage systems is of great significance. Compared with organic electrolyte batteries, aqueous rechargeable energy storage devices have higher operational safety and lower cost, and have received more and more attention. Among them, aqueous zinc-iodine batteries have high theoretical capacity, low redox potential, stable chemical properties and abundant resources, and have good application prospects. As a multivalent electrode material, iodine electrode is abundant in source and has a large capacity (422 mAh g -1 , based on I - —I + However, in aqueous electrolytes, iodine ions (I + ) intermediate, which has certain oxidizing properties and is easily hydrolyzed in water, resulting in low coulombic efficiency. - 、I3 - 、I5 - ) will lead to the loss of active species, eventually causing capacity decay and short cycle life, limiting the further development of zinc-iodine batteries.

[0003] Currently, researchers have developed high-concentration electrolytes and eutectic electrolytes to stabilize I + , reducing the occurrence of side reactions. At the same time, these electrolytes have a relatively high viscosity, which can inhibit the water-soluble intermediates (I - 、I3 - 、I5 - ) shuttle. However, these electrolytes are expensive, easy to freeze at low temperatures and have high viscosity, which ultimately leads to sluggish reaction kinetics and poor electrochemical performance of zinc-iodine batteries. Therefore, in addition to improving the electrolyte, the positive and negative electrodes can also be improved. For example, designing a better positive electrode material can effectively capture and stabilize these discharge process intermediates (I - 、I3 - 、I5 - ), thereby avoiding the shuttle effect of intermediates in the electrolyte. If a two-dimensional layer is added to the positive electrode, the contact area with the electrolyte can be increased, the ion diffusion path can be shortened, and the kinetic performance can be improved. Layered materials have a periodic layered structure and a two-dimensional ion transmission channel, which increases the ion transmission rate; layered materials have strong structural stability and can better maintain their integrity during the charge and discharge process without significant volume changes or structural collapse, thus providing a stable environment for the continuous transmission of ions.

[0004] When it comes to two-dimensional layered materials, the most easily thought of are inorganic materials such as graphene, boron nitride, and MoS2. In particular, there are many reports on the use of graphene as an electrode material. However, graphene has low strength and few active sites. It is difficult to inhibit the water-soluble intermediates (I - 、I3 - 、I5 - ). Therefore, it is necessary to develop more positive electrode materials with layered structures for the preparation of more stable zinc-iodine batteries, reduce the obstacles encountered by ions when moving between layers in aqueous electrolytes, inhibit the shuttling ability of water-soluble intermediates, and improve the cycle stability and service life of the battery. Summary of the invention

[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide a zinc-iodine battery with coordinated stability of inorganic / organic hybrid materials and its application. The present invention fully mixes the inorganic layered material zirconium hydrogen phosphate (ZPO) and the cyclic two-dimensional organic material phthalocyanine (PC) to form an inorganic-organic hybrid interface layer to make a positive electrode sheet, and combines the high strength and high modulus of ZPO with the flexibility of PC to significantly improve the phase interface fusion of the composite material ZPO / PC, thereby improving the cycle stability and service life of the battery.

[0006] To achieve the above object, the present invention adopts the following technical solution: The first aspect of the present invention provides a zinc-iodine battery synergistically stabilized by inorganic / organic hybrid materials, the zinc-iodine battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; the positive electrode sheet contains an inorganic / organic hybrid material composed of a layered inorganic material and a ring-shaped two-dimensional organic material.

[0007] Preferably, the positive electrode sheet is prepared by the following method: (1) Fully mixing the layered inorganic material and the cyclic two-dimensional organic material to obtain an inorganic / organic hybrid material; (2) The inorganic / organic hybrid material, conductive carbon and binder are ground and mixed, coated on the current collector and then dripped with I - Active material solution to obtain a positive electrode sheet.

[0008] Preferably, in step (1), the layered inorganic material is zirconium hydrogen phosphate; and the cyclic two-dimensional organic material is phthalocyanine. The chemical formula of phthalocyanine is C 32 H 18 N8.

[0009] Preferably, in step (1), the mass ratio of the layered inorganic material to the cyclic two-dimensional organic material is 1:1.

[0010] Preferably, in step (1), the sufficient mixing is ball milling or dissolution; the dissolution is specifically: adding the cyclic two-dimensional organic material to an organic solvent to dissolve it, then adding the layered inorganic material, and after dissolution, evaporating and removing the organic solvent to obtain an inorganic / organic hybrid material.

[0011] The organic solvent is anhydrous ethanol.

[0012] Preferably, in step (2), the mass ratio of the inorganic / organic hybrid material, the conductive carbon and the binder is 8:1:1.

[0013] The conductive carbon is acetylene black, and the binder is PVDF.

[0014] Preferably, the I - Active substance solution contains I - The active substance is selected from lithium iodide, sodium iodide, potassium iodide, ammonium iodide or copper iodide.

[0015] Preferably, the I - Active substance solution contains I - The concentration of active substances is 0.1~4.0M.

[0016] Preferably, the negative electrode sheet is zinc foil; and the electrolyte is zinc trifluoromethanesulfonate solution.

[0017] The second aspect of the present invention provides the application of the zinc-iodine battery in improving the cycle stability and service life of the battery.

[0018] Beneficial effects of the present invention: (1) The present invention uses inorganic layered material ZPO and annular two-dimensional organic material PC to fully mix to form an inorganic-organic hybrid interface layer, and combines the high strength and high modulus of ZPO material with the flexibility of PC material to significantly improve the interface fusion of the composite material ZPO / PC. This not only solves the problem of I + The unstable intermediates improve the coulombic efficiency of the battery. At the same time, the cyclic conjugated system of PC can effectively capture and stabilize the intermediates (I - 、I3 - 、I5 - ), thereby avoiding the shuttle effect of intermediates in the electrolyte and improving the cycle performance of the battery. This unique innovative idea provides a simple and reliable method to improve the comprehensive performance of zinc-iodine batteries, brings new opportunities for the development of energy storage, and promotes the development of energy storage equipment in the direction of high efficiency, environmental friendliness and safety.

[0019] (2) ZPO in the positive electrode of the present invention is a layered material with a large specific surface area and surface charge, which can be well connected with the intermediate I during the charging process.+ Ion binding, stabilization of I + ions, reducing their side reactions and improving the battery coulombic efficiency. The present invention utilizes the PC material with a cyclic 18-electron large conjugated system to effectively capture and stabilize the intermediates (I - 、I3 - 、I5 - ), achieving the effect of synergistically stabilizing the zinc-iodine battery intermediate. The present invention can directly use I⁻ as an electrode material with the help of this inorganic / organic hybrid material, which is more conducive to the application of large-scale energy storage of zinc-iodine batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The ordinary zinc-iodine battery prepared in Comparative Example 1 was -1 The charge and discharge curves of the first 5 cycles under current density; Figure 2 is the X-ray diffraction spectrum of ZPO in Comparative Example 2; Figure 3 The scanning electron microscope images and mapping images of ZPO in comparative example 2; (a) to (c) are scanning electron microscope images of ZPO at different magnifications; (d) is the mapping image of the Zr element; (e) is the mapping image of the P element; (f) is the mapping image of the O element; Figure 4 The inorganic zinc-iodine battery prepared in Comparative Example 2 was -1 The charge and discharge curves of the first 5 cycles under current density; Figure 5 The inorganic zinc-iodine battery prepared in Comparative Example 2 was -1 Battery performance graph for 1-100 cycles under current density; Figure 6 This is a diagram of the stability mechanism of ZPO in the inorganic material zinc-iodine battery prepared in Comparative Example 2; Figure 7 is the X-ray diffraction spectrum of PC in Comparative Example 3; Figure 8 The scanning electron microscope images and mapping images of PC in comparative example 3; (a) to (c) are scanning electron microscope images of PC at different magnifications; (d) is the mapping image of the C element; (e) is the mapping image of the N element; (f) is the mapping image of the O element; Fig. 9 The organic zinc-iodine battery prepared in Comparative Example 3 was -1 The charge and discharge curves of the first 5 cycles under current density; Fig.10 The organic material zinc-iodine battery prepared in Comparative Example 3 was-1 Battery performance graph for 1-100 cycles under current density; Fig.11 This is a diagram of the stabilization mechanism of PC in the organic material zinc-iodine battery prepared in Comparative Example 3; Fig.12 X-ray diffraction spectrum of the ZPO / PC hybrid material prepared in Example; Fig.13 The scanning electron microscope images and mapping images of the ZPO / PC hybrid material prepared in the example; (a) to (c) are scanning electron microscope images of the ZPO / PC hybrid material at different magnifications; (d) is the mapping image of the C element; (e) is the mapping image of the N element; (f) is the mapping image of the O element; (g) is the mapping image of the Zr element; (h) is the mapping image of the P element; Fig.14 The inorganic / organic hybrid material prepared in this example synergistically stabilizes the zinc-iodine battery at 0.5A g -1 The charge and discharge curves of the first 5 cycles under current density; Fig.15 The inorganic / organic hybrid material prepared in this example synergistically stabilizes the zinc-iodine battery at 2 A g -1 Battery performance graph for 1-100 cycles under current density. DETAILED DESCRIPTION

[0021] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0022] As introduced in the background technology section, under normal conditions, zinc-iodine batteries use iodine as the active substance. However, the use of iodine requires solvent thermal or sublimation methods to prepare it into electrode sheets, that is, "iodine filling" is required to make electrode sheets, and the reaction must be carried out at high temperature.

[0023] Based on this, the purpose of the present invention is to provide a zinc-iodine battery with coordinated stability of inorganic / organic hybrid materials and its application. The present invention fully mixes the inorganic layered material zirconium hydrogen phosphate (ZPO) and the cyclic two-dimensional organic material phthalocyanine (PC) to form an inorganic-organic hybrid interface layer. Zirconium hydrogen phosphate (ZPO) is a new multifunctional mesoporous material and one of the layered solid acid materials. It has a large specific surface area and surface charge, good ion exchange properties, high thermal stability and acid and alkali resistance. Therefore, ZPO can be well combined with I + Ionic bonding, solidification +ions, reducing their side reactions and improving the coulombic efficiency of the battery. At the same time, phthalocyanine (PC) has a unique cyclic 18-electron conjugated system, and it is easy to form a two-dimensional layered structure between molecules. The cyclic conjugated system can effectively capture and stabilize the intermediates (I - 、I3 - 、I5 - ), thereby avoiding the shuttle effect of intermediates in the electrolyte. When ZPO is used alone to prepare the positive electrode sheet, it cannot inhibit the shuttle of water-soluble intermediates. When PC is used alone to prepare the positive electrode sheet, the strength is not enough and it is not compatible with I + Due to the insufficient ion binding ability, the performance of the positive electrode prepared by these two materials alone is difficult to meet the requirements. However, by combining the high strength and high modulus of ZPO material with the flexibility of PC material to prepare the positive electrode, the layered ZPO and layered PC materials can be fully mixed between molecules, making the mixing more uniform, realizing a large number of uniform inorganic-organic phase interfaces, and improving the phase interface fusion of the composite material ZPO / PC. During the charge and discharge process, the layered structure can better maintain its integrity, without significant volume changes or structural collapse, and can provide more active sites for adsorption, so that the prepared zinc-iodine battery has better cycle stability and longer service life. In addition, when preparing the positive electrode, the inorganic-organic hybrid interface layer formed by the inorganic layered material zirconium hydrogen phosphate (ZPO) and the cyclic two-dimensional organic material phthalocyanine (PC) does not need to be "irrigated" at high temperature. It only needs to drip lithium iodide, sodium iodide, potassium iodide, ammonium iodide or copper iodide and other I-containing materials on the inorganic-organic hybrid interface layer. - The active substance solution, that is, greatly reduces the difficulty and safety of preparation and simplifies the preparation process.

[0024] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0025] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0026] Example: Preparation of inorganic / organic hybrid materials for synergistically stabilized zinc-iodine batteries S1. Preparation of inorganic / organic hybrid material: 200 mg PC powder was added to 100 mL anhydrous ethanol and dissolved after ultrasonication for 20 min. Then 200 mg ZPO powder was added thereto and ultrasonication was performed for 20 min to fully disperse ZPO in the ethanol solution so that it could fully contact with the dissolved PC. The solution was evaporated to dryness on a heating table at 50°C to obtain an inorganic / organic hybrid material, which was recorded as ZPO / PC hybrid material.

[0027] S2, Preparation of positive electrode sheet: Put the ZPO / PC hybrid material (80 mg), conductive carbon acetylene black (10 mg) and binder PVDF (10 mg) prepared in S1 into a mortar, add 200 μL N-methylpyrrolidone (NMP), grind and mix thoroughly, apply it on a round titanium foil metal (diameter: 10 mm, thickness: 100 μm) current collector, and dry it at 70°C in vacuum for 8 h. Then, add 80 μL of 0.2 M potassium iodide solution on its surface, let it stand and dry at room temperature to make the active material I - Fully contact and enter the interior of the electrode material to obtain a positive electrode sheet.

[0028] S3. Assembly of zinc-iodine battery: Use zinc foil (diameter: 10 mm; thickness: 100 μm) as the negative electrode, zinc trifluoromethanesulfonate (concentration of 3M, 150 μL) as the electrolyte, and glass fiber (diameter: 16 mm; thickness: 100 μm) as the separator, and assemble it with the positive electrode sheet prepared in S2 to obtain a 2032 battery, which is a zinc-iodine battery synergistically stabilized by inorganic / organic hybrid materials, and test its electrochemical properties.

[0029] Fig.12 This is the XRD spectrum of the ZPO / PC hybrid material prepared in Example S1. Its characteristic peak is an obvious characteristic peak of ZPO, and a PC peak appears near 5°, which proves that the hybrid material is successfully composited.

[0030] Fig.13 This is the SEM image of the ZPO / PC hybrid material prepared in Example S1. The ZPO layer is still maintained, and its surface becomes rough, which is due to the composite PC material. Zr, P, C, N and O elements are evenly distributed in the sample.

[0031] Fig.14 The inorganic / organic hybrid material prepared in this example synergistically stabilizes the zinc-iodine battery at 0.5A g -1 The charge and discharge curves of the first five cycles, the initial discharge capacity is 235 mAh g -1 After 5 cycles, the capacity becomes 227 mAh g -1 , the coulombic efficiency can still be maintained at 99%. Both the capacity and coulombic efficiency are higher than those of comparative example 1, and the coulombic efficiency and cycle have been greatly improved.

[0032] Fig.15 The inorganic / organic hybrid material synergistically stabilized zinc-iodine battery prepared in this example has a current density of 2 Ag. -1 The 100-cycle long cycle curve shows that the battery discharge capacity increases from 138 mAh g -1 Down to 130 mAh g -1The coulombic efficiency was maintained at 99%, indicating that the ZPO / PC hybrid material can synergistically stabilize the zinc-iodine battery intermediate (I + ,I - 、I3 - 、I5 - ), improve the electrochemical performance of the battery.

[0033] The schematic diagram of its stabilization mechanism is as follows Figure 6 and Fig.11 As shown, due to the hydrogen ions in the ZPO structure and I + It is easy to exchange between them, and ZPO can effectively stabilize I + , inhibiting its hydrolysis reaction. On the other hand, the conjugated system in the PC ring structure can adsorb the intermediate (I - 、I3 - 、I5 - ), inhibiting its dissolution in water, thereby improving the stability of the battery.

[0034] Comparative Example 1: Preparation of a common zinc-iodine battery S1. Preparation of positive electrode: put the conductive carbon acetylene black (90 mg) and the binder PVDF (10 mg) into a mortar, add 200 μL of NMP solvent, grind and mix thoroughly, apply it on a round titanium foil metal (diameter: 10 mm; thickness: 100 μm) current collector, and dry it at 70℃ in vacuum for 8 h. Then, add 80 μL of potassium iodide solution (0.2 M) on its surface and let it stand and dry at room temperature to make the active material I - Fully contact and enter the interior of the electrode material.

[0035] S2. Assembly of zinc-iodine battery: Use the positive electrode sheet prepared in S1, zinc foil (diameter: 10 mm; thickness: 100 μm) as the negative electrode, zinc trifluoromethanesulfonate (3M, 150 μL) as the electrolyte, and glass fiber (diameter: 16 mm; thickness: 100 μm) as the separator to assemble a 2032 battery, which is a common zinc-iodine battery, and test its electrochemical performance.

[0036] Figure 1 The zinc-iodine battery prepared in Comparative Example 1 has a -1 The charge and discharge curves of the first five cycles show a Coulomb efficiency of about 93% and a discharge capacity of 23 mAh g -1 After only 5 cycles, the capacity dropped to 16.5 mAh g -1 , indicating that zinc-iodine batteries using potassium iodide as the active material without the synergistic stabilization of inorganic / organic hybrid materials have serious side reactions and shuttle effects, leading to poor battery performance.

[0037] Comparative Example 2: Preparation of Inorganic Material Zinc-Iodine Battery S1. Preparation of positive electrode sheet: ZPO (80 mg), conductive carbon acetylene black (10 mg) and binder PVDF (10 mg) were placed in a mortar, 200 μL NMP was added, and the mixture was fully ground and mixed. The mixture was then coated on a round titanium foil (diameter: 10 mm; thickness: 100 μm) current collector and dried at 70°C in vacuum for 8 h. Subsequently, 80 μL of potassium iodide solution (0.2 M) was added to the surface of the current collector and the mixture was left to dry at room temperature to allow the active material I - Fully contact and enter the interior of the electrode material.

[0038] S2. Assembly of zinc-iodine battery: Use the prepared positive electrode sheet, zinc foil (diameter: 10 mm; thickness: 100 μm) as the negative electrode, zinc trifluoromethanesulfonate (3M, 150 μL) as the electrolyte, and glass fiber (diameter: 16 mm; thickness: 100 μm) as the separator to assemble the 2032 battery, which is the inorganic zinc-iodine battery, and test its electrochemical properties.

[0039] Figure 2 This is the XRD spectrum of ZPO in Comparative Example 2. Its characteristic peaks are consistent with those of the standard card, and there are no additional characteristic peaks, which proves that ZPO is a pure phase.

[0040] Figure 3 This is the SEM image of ZPO in Comparative Example 2. ZPO presents lamellae with a size of approximately 0.5-1.5 μm. Zr, P and O elements are evenly distributed in the sample, proving that ZPO is a uniform layered material.

[0041] Figure 4 The inorganic zinc-iodine battery prepared in Comparative Example 2 was -1 The charge and discharge curves of the first five cycles show a Coulomb efficiency of 99%. Compared with comparative example 1, the introduction of ZPO is beneficial to stabilize I + ions, reduce their side reactions and improve the coulombic efficiency of the battery.

[0042] Figure 5 The inorganic zinc-iodine battery prepared in Comparative Example 2 was -1 The 100-cycle long cycle curve shows that the battery discharge capacity increases from 78 mAh g to -1 Down to 66 mAh g -1 , the coulomb efficiency is 98%, indicating that ZPO is beneficial to stabilize I + Intermediates, improve coulombic efficiency.

[0043] The schematic diagram of its stabilization mechanism is as follows Figure 6 As shown, due to the hydrogen ions in the ZPO structure and I + It is easy to exchange between them, and ZPO can effectively stabilize I+ , inhibiting its hydrolysis reaction, thereby improving the coulombic efficiency.

[0044] Comparative Example 2 shows two obvious platforms in the charge-discharge curve, indicating that ZPO can effectively stabilize I + , can achieve I - —I + The two-step reaction has also improved the capacity and coulombic efficiency. - 、I3 - 、I5 - ) Due to the shuttle effect, the cycle performance is poor and still attenuated. However, the use of inorganic-organic hybrid materials in the embodiment can improve the capacity and coulombic efficiency while greatly improving the cycle performance.

[0045] Comparative Example 3: Preparation of organic material zinc-iodine battery S1. Preparation of positive electrode sheet: PC (80 mg), conductive carbon acetylene black (10 mg) and binder PVDF (10 mg) were placed in a mortar, 200 μL NMP was added, and the mixture was fully ground and mixed. The mixture was then coated on a round titanium foil (diameter: 10 mm; thickness: 100 μm) current collector and dried at 70°C in vacuum for 8 h. Subsequently, 80 μL of potassium iodide solution (0.2 M) was added to the surface of the current collector and the mixture was left to dry at room temperature to allow the active material I - Fully contact and enter the interior of the electrode material.

[0046] S2. Assembly of zinc-iodine battery: Use the prepared positive electrode sheet, zinc foil (diameter: 10 mm; thickness: 100 μm) as the negative electrode, zinc trifluoromethanesulfonate (3M, 150 μL) as the electrolyte, and glass fiber (diameter: 16 mm; thickness: 100 μm) as the separator to assemble the 2032 battery, which is the organic material zinc-iodine battery, and test its electrochemical performance.

[0047] Figure 7 This is the XRD spectrum of PC in Comparative Example 3. The presence of its characteristic peaks indicates the π-π conjugated structure in the organic material PC molecule.

[0048] Figure 8 This is the SEM image of PC in Comparative Example 3. PC appears to be granular, and C, N and O elements are evenly distributed in the sample.

[0049] Fig. 9 The organic zinc-iodine battery prepared in Comparative Example 3 was -1 The charge and discharge curves of the first five cycles, the initial discharge capacity is 138 mAh g -1 After 5 cycles, the capacity becomes 101 mAh g -1The capacity is higher than that of comparative example 1, and the cycle is improved significantly.

[0050] Fig.10 The organic zinc-iodine battery prepared in Comparative Example 3 was -1 The 100-cycle long cycle curve shows that the battery discharge capacity increases from 97 mAh g -1 Down to 85 mAh g -1 , indicating that PC can effectively capture and stabilize the intermediates of these discharge processes (I - 、I3 - 、I5 - ), improve the battery cycle performance.

[0051] The schematic diagram of its stabilization mechanism is as follows Fig.11 As shown, the conjugated system in the PC ring structure can adsorb the intermediate (I - 、I3 - 、I5 - ), inhibiting its dissolution in water, thereby improving the stability of the battery.

[0052] In the cycle performance diagram of comparative example 3, it can be seen that PC can adsorb the intermediates (I - 、I3 - 、I5 - ), inhibiting the shuttle effect and improving the cycle performance of the battery. However, only one obvious platform appeared in the charge-discharge curve, and the high potential platform was not obvious. This is because the PC material cannot stabilize the intermediate I + ions, therefore, the capacity of Comparative Example 3 is relatively lower than that of the embodiment. The use of inorganic-organic hybrid materials in the embodiment can improve the cycle performance, and the capacity and coulombic efficiency are also greatly improved.

[0053] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A zinc-iodine battery with coordinated stabilization of inorganic / organic hybrid materials, characterized in that: The zinc-iodine battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; the positive electrode sheet contains an inorganic / organic hybrid material composed of a layered inorganic material and a ring-shaped two-dimensional organic material.

2. The zinc-iodine battery according to claim 1, characterized in that: The positive electrode sheet is prepared by the following method: (1) Fully mixing the layered inorganic material and the cyclic two-dimensional organic material to obtain an inorganic / organic hybrid material; (2) The inorganic / organic hybrid material, conductive carbon and binder are ground and mixed, coated on the current collector and then dripped with I - Active material solution to obtain a positive electrode sheet.

3. The zinc-iodine battery according to claim 2, characterized in that: In step (1), the layered inorganic material is zirconium hydrogen phosphate; and the cyclic two-dimensional organic material is phthalocyanine.

4. The zinc-iodine battery according to claim 2, characterized in that: In step (1), the mass ratio of the layered inorganic material to the cyclic two-dimensional organic material is 1:

1.

5. The zinc-iodine battery according to claim 2, characterized in that: In step (1), the sufficient mixing is ball milling or dissolution separation; The dissolution separation is specifically as follows: adding the cyclic two-dimensional organic material into an organic solvent to dissolve it, then adding the layered inorganic material, and after the material is dissolved, evaporating and removing the organic solvent to obtain the inorganic / organic hybrid material.

6. The zinc-iodine battery according to claim 2, characterized in that: In step (2), the mass ratio of the inorganic / organic hybrid material, the conductive carbon and the binder is 8:1:

1.

7. The zinc-iodine battery according to claim 2, characterized in that: In step (2), the I - Active substance solution contains I - The active substance is selected from lithium iodide, sodium iodide, potassium iodide, ammonium iodide or copper iodide.

8. The zinc-iodine battery according to claim 7, characterized in that: I - Active substance solution contains I - The concentration of active substances is 0.1~4.0M.

9. The zinc-iodine battery according to claim 1, characterized in that: The negative electrode sheet is zinc foil; the electrolyte is zinc trifluoromethanesulfonate solution.

10. Application of the zinc-iodine battery according to any one of claims 1 to 9 in improving the cycle stability and service life of the battery.

Citation Information

Patent Citations

  • Lithium battery with composite structure

    CN116454231A

  • Preparation of zinc-phthalocyanine composite negative electrode material and application of zinc-phthalocyanine composite negative electrode material in zinc battery

    CN117374240A

  • Molecular catalyst / activated carbon composite material as well as preparation method and application thereof

    CN118919724A

  • Rechargeable lithium cell having a phthalocyanine-based high-capacity cathode

    US20130309561A1